GR-RMHD Simulations of Super-Eddington Accretion Flows onto a Neutron Star with Dipole and Quadrupole Magnetic Fields - Akihiro Inoue; Ken Ohsuga; Hiroyuki R. Takahashi; Yuta Asahina; Matthew J. Middleton (The Astrophysical Journal)
Although ultraluminous X-ray pulsars (ULXPs) are believed to be powered by super-Eddington accretion onto a magnetized neutron star (NS), the detailed structures of the inflow–outflow and magnetic fields are still not well understood. We perform general relativistic radiation magnetohydrodynamics (GR-RMHD) simulations of super-Eddington accretion flows onto a magnetized NS with dipole and/or quadrupole magnetic fields. Our results show that an accretion disk and optically thick outflows form outside the magnetospheric radius, while inflows aligned with magnetic field lines appear inside. When the dipole field is more prominent than the quadrupole field at the magnetospheric radius, accretion columns form near the magnetic poles, whereas a quadrupole magnetic field stronger than the dipole field results in the formation of a belt-like accretion flow near the equatorial plane. The NS spins up as the angular momentum of the accreting gas is converted into the angular momentum of the electromagnetic field, which then flows into the NS. Even if an accretion column forms near one of the magnetic poles, the observed luminosity is almost the same on both the side with the accretion column and the side without it, because the radiation energy is transported to both sides through scattering. Our model suggests that galactic ULXP Swift J0243.6+6124 has a quadrupole magnetic field of 2 × 10 ^13 G and a dipole magnetic field of less than 4 × 10 ^12 G.